The effect of fluoride use, oral healthcare behavior, and water sources on the prevalence of dental caries in preschool-aged children in Thailand - Kanyarat Korwanich; Narumanas Korwanich; Chittraphone Chakkrawan (Dental Journal (Majalah Kedokteran Gigi), 2026)
Background: Since Thailand’s government implemented a regulation allowing 1,500 ppm of fluoride in over-the-counter toothpastes, a few studies have explored behaviors related to fluoride intake in areas high in natural fluoride. Purpose: This study aims to explore toothbrushing habits, water sources used for meal preparation, and toothpaste use among 4–5-year-olds to determine how these factors influence the prevalence of dental caries in preschool-aged children in areas with naturally occurring high levels of fluoride. Methods: A self-reporting questionnaire was prepared and distributed to the parents of 304 4–5-year-old schoolchildren in the Lamphun province of Thailand. The questionnaire was designed to assess toothbrushing habits, water sources used for meal preparation, and toothpaste use among young schoolchildren. Dental caries data were obtained from the annual school record of each child. Statistical analysis was performed to test the association between oral healthcare habits and dental caries prevalence at a significance level of 0.05. Results: More than ninety-five percent of respondents used fluoridated toothpaste with concentrations of 1,000–1,500 ppm, and 57.9% rinsed their mouths thoroughly after toothbrushing (i.e., until they “felt clean”). Most parents used bottled water for drinking, mixing milk, and cooking. Significant associations were found between dental caries prevalence and the use of fluoridated toothpaste; toothpaste fluoride concentrations; and water sources used for cooking, drinking, and mixing infant formula (p < 0.05). Conclusion: Despite living in an area with naturally high fluoride levels in water sources, most children used fluoridated toothpaste to prevent dental caries and bottled water with a lower fluoride concentration for cooking and drinking. The common practice of thoroughly rinsing the mouth with water highlights the need for advocacy around proper practices to effectively maintain fluoride ions in the oral cavity.